ORIGINAL PAPER Summer temperatures during the Medieval Warm Period and Little Ice Age inferred from varved proglacial lake - Michael G. Loso
Abstract For the heavily glaciated mountains of southern Alaska, few high-resolution, millennial-scale proxy temperature reconstructions are available for comparison with modern temperatures or with the history of glacier fluctuations. Recent catastrophic drainage of glacier-dammed Iceberg Lake, on the northern margin of the Bagley Icefield, exposed subaerial outcrops of varved lacustrine sediments that span the period 442–1998 AD. Here, an updated chronology of varve thickness measurements is used to quantitatively reconstruct melt-season temperature anomalies. From 1958 to 1998, varve thickness has a positive and marginally significant correlation with May–June temperatures at the nearest coastal mea-surement stations. Varve sensitivity to temperature has changed over time, however, in response to lake level changes in 1957 and earlier. I compensate for this by log-transforming the varve thickness chronology, and also by using a 400-year-long tree-ring-based temperature proxy to reconstruct melt-season temperatures at Iceberg Lake. Regression against this longer proxy record is statistically weak, but spans the full range of occupied lake levels and varve sensitivities. Reconstructed temperature anom-alies have broad confidence intervals, but nominally span 1.1C over the last 1500? years. Maximum temperatures occurred in the late twentieth century, with a minimum in the late sixth century. The Little Ice Age is present as three cool periods between 1350 and 1850 AD with maximum cooling around 1650 AD. A Medieval Warm Period is evident from 1000 to 1100 AD, but the temperature reconstruction suggests it was less warm than recent decades—an observation supported by independent geological evidence of recent glacier retreat that is unprece-dented over the period of record.